Konstruksi Model Pembelajaran STEAM (Science, Technology, Engineering, Arts, and Mathematics) dengan Pendekatan Design Thinking pada Materi Energi Terbarukan - Devie Febriansari; Sarwanto Sarwanto; Sri Yamtinah (JINoP (Jurnal Inovasi Pembelajaran), 2022)
Industrial revolution 4.0 accelerates the need for resources with contextual skills relevant to technological advances. Renewable energy is one of the global issues that need to be followed up into one of the concerns in education. The STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning concept is seen as a learning innovation that accommodates the skills needed in the era of the industrial revolution 4.0. In addition, through the design thinking approach, students are facilitated to realize creativity or ideas in solving surrounding problems. This study aims to reconstruct the STEAM learning model with a combination of design thinking approaches to renewable energy learning materials. This research uses a descriptive qualitative approach to data sources from the literature. The analysis tool used is Miles and Huberman interactive model data analysis. The purpose of this research is to formulate a combined framework of the STEAM learning model and design thinking that can be applied to renewable energy learning materials.